2020
DOI: 10.1101/2020.01.07.897454
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Basal-like and Classical cells coexistence in pancreatic cancer revealed by single cell analysis

Abstract: 26Pancreatic ductal adenocarcinoma (PDAC) is composed of stromal, immune and epithelial 27 cells. Transcriptomic analysis of the epithelial compartment allows a binary classification into 28 mainly two phenotypic subtypes, classical and basal-like. However, little is known about the 29 intra-tumor heterogeneity of the epithelial component. Growing evidences suggest that this 30 two side phenotypic segregation is not so clear and that both could coexist in a single tumor. In 31 order to elucidate this hypothesi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 41 publications
3
21
0
Order By: Relevance
“…To categorize transcriptional heterogeneity in PDAC, an established classification scheme distinguishes 'classical' from 'basal-like' tumors. In line with recent results from other groups 17,39 , our cohort comprised PDAC organoids with uniformly 'classical' gene expression, but also a subset of organoids with heterogeneous expression of subtype marker genes across cells. The latter were associated with a poorer prognosis of the patient, as determined by histopathological grading of the original tumor.…”
Section: Discussionmentioning
confidence: 58%
“…To categorize transcriptional heterogeneity in PDAC, an established classification scheme distinguishes 'classical' from 'basal-like' tumors. In line with recent results from other groups 17,39 , our cohort comprised PDAC organoids with uniformly 'classical' gene expression, but also a subset of organoids with heterogeneous expression of subtype marker genes across cells. The latter were associated with a poorer prognosis of the patient, as determined by histopathological grading of the original tumor.…”
Section: Discussionmentioning
confidence: 58%
“…Recent single-cell analyses have demonstrated the coexistence of basal-like and classical subtypes within a single tumor with the relative proportions of these cells determining the overarching subtype at the bulk transcriptome level (19,38). In another recent study, evolutionary analysis of mixed phenotype tumors, comprising classical and basal-like features, from autopsy patients revealed that the basallike subtype represented a subclone contained within an otherwise classical tumor (18).…”
Section: Transcriptional Shift Is Governed By Tumor Cell Plasticity Imentioning
confidence: 99%
“…We have made similar observations in this study. VIM, which is mainly expressed in basal-like subtype, was detected by immunohistochemistry in almost all classical tumors, with variable levels of expression [17]. We detected few VIM+ cells in tumors presenting an intermediate PAMG.…”
Section: Discussionmentioning
confidence: 60%
“…the infiltrated Immunogenic subtype), and delineated a consensual basal-like versus classical dichotomy. However, this two-subtype classification system of PDAC has recently been challenged by several studies showing the coexistence of basal-like and classical cells in the same tumors as well as to the likely existence of intermediate cellular phenotypes [15,17]. In this study, we have used a gradient system that takes this into consideration to classify PDAC.…”
Section: Discussionmentioning
confidence: 99%